Pengaruh Konsentrasi Starter dan Gula terhadap Karakteristik Wine Jahe - Rahmasari, Emma; Wisaniyasa, Ni Wayan; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPA, 2022)
This research was aimed to determine the effect of starter and sugar concentration on the characteristics of ginger wine and to determine the optimal concentration of starter and sugar to obtain the best characteristics of ginger wine. This study used a Completely Randomized Design with two factors. The first factor was the concentration of starter namely: 10, 15, and 20% (v/v), and the second factor was sugar concentration, namely: 20, 25, and 30% (w/v). The parameter tested were alcohol (ethanol) level, reducing sugar, total acid, acidity (pH), total soluble solid, as well as the sensory evaluation with hedonic tests on the color, smell, taste, overall acceptance, and scoring tests on the sweet and bitter tasted. The results showed that the interaction between the concentration of starter and sugar had a significant effect on reducing sugar, total acid, and total soluble solids, but the interaction did not have a significant effect on the ethanol level and pH, only showed the significant effect against the concentration of starter and sugar. Ginger wine with the best characteristics was obtained from combination starter concentration of 15% (v/v) and sugar 25% (w/v) with ethanol level, reducing sugar, total acid, pH and total soluble solid of wine were 8,78%; 1,60oBrix, 0,30%, 3,54 and 7,65%, respectively; and with the color and aroma liked, ordinary taste, slightly sweet, bitter, and overall acceptance liked.